Financial and recovery worry one year after traumatic injury: A prognostic, registry-based cohort study. Issue 5 (May 2018) - Ioannou, L.; Cameron, P.A.; Gibson, S.J.; Ponsford, J.; Jennings, P.A.; Georgiou-Karistianis, N.; Giummarra, M.J.
Abstract: Background: Levels of stress post-injury, especially after compensable injury, are known to be associated with worse long-term recovery. It is therefore important to identify how, and in whom, worry and stress manifest post-injury. This study aimed to identify demographic, injury, and compensation factors associated with worry about financial and recovery outcomes 12 months after traumatic injury. Methods: Participants ( n = 433) were recruited from the Victorian Orthopaedic Trauma Outcomes Registry and Victorian State Trauma Registry after admission to a major trauma hospital in Melbourne, Australia. Participants completed questionnaires about pain, compensation experience and psychological wellbeing as part of a registry-based observational study. Results: Linear regressions showed that demographic and injury factors accounted for 11% and 13% of variance in financial and recovery worry, respectively. Specifically, lower education, discharge to inpatient rehabilitation, attributing fault to another and having a compensation claim predicted financial worry. Worry about recovery was only predicted by longer hospital stay and attributing fault to another. In all participants, financial and recovery worry were associated with worse pain (severity, interference, catastrophizing, kinesiophobia, self-efficacy), physical (disability, functioning) and psychological (anxiety, depression, PTSD, perceived injustice) outcomes 12 months post-injury. In participants who had transport ( n = 135) or work ( n = 22) injury compensation claims, both financial and recovery worry were associated with sustaining permanent impairments, and reporting negative compensation system experience 12 months post-injury. Financial worry 12 months post-injury was associated with not returning to work by 3–6 months post-injury, whereas recovery worry was associated with attributing fault to another, and higher healthcare use at 6–12 months post-injury. Conclusions: These findings highlight the important contribution of factors other than injury severity, to worry about finances and recovery post-injury. Having a compensation claim, failure to return to work and experiencing pain and psychological symptoms also contribute to elevated worry. As these factors explained less than half of the variance in worry, however, other factors not measured in this study must play a role. As worry may increase the risk of developing secondary mental health conditions, timely access to financial, rehabilitation and psychological supports should be provided to people who are not coping after injury.